2021
DOI: 10.24843/metamorfosa.2021.v08.i01.p05
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Ekstrak Hipofisa Ayam Broiler (Gallus sp.) Terhadap Kinerja Reproduksi Dan Kelulushidupan Larva Ikan Lele Sangkuriang (Clarias sp.)

Abstract: Kelenjar hipofisa ayam broiler (Gallus sp.) secara empiris diketahui memiliki gonadotropin untuk mempercepat ovulasi pada ikan. Penelitian ini dilakukan untuk mengetahui kinerja reproduksi dan kelulushidupan larva ikan lele sangkuriang (Clarias sp.) jantan dan betina dewasa yang matang gonad sebanyak 20 pasang. Penelitian ini menggunakan Rancangan Acak Lengkap terdiri atas 4 perlakuan dan 5 ulangan sehingga diperoleh 20 unit percobaan. Dosis ekstrak hipofisa yang digunakan adalah tanpa penyuntikan ekstrak hipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…While the chicken 1221 (2023) 012008 IOP Publishing doi:10.1088/1755-1315/1221/1/012008 4 or duck pituitary extract is not pure, the concentration is also not known, maybe the amount was not sufficient to stimulate the ovulation process in climbing perch. Lesik and Ermayanti [27] added that the accuracy of the dose of pituitary extract greatly determines the success of the fish ovulation process, where the highest dose (1200 mg/kgbb) of broiler pituitary extract gave better results than the doses of 600 and 900 mg/kgbb for Clarias sp., it is suspected that the gonadotropin hormone in the blood will increase with increasing doses injected. Note: A = 0.5 ml/kg BW of Ovaprim (control), B= 0.5 ml/kg BW of chicken pituitary extract, C= 0.5 ml/kg BWof duck pituitary extract, D= 0.25 ml/kg BW of chicken pituitary extract + 0.25 ml/kg BW of duck However, the results showed that the use of local chicken and duck pituitary gland extracts could trigger ovulation in climbing perch, therefore, the local chicken and duck pituitary gland extracts of these avians can be used as an alternative when Ovaprim is not available.…”
Section: Resultsmentioning
confidence: 99%
“…While the chicken 1221 (2023) 012008 IOP Publishing doi:10.1088/1755-1315/1221/1/012008 4 or duck pituitary extract is not pure, the concentration is also not known, maybe the amount was not sufficient to stimulate the ovulation process in climbing perch. Lesik and Ermayanti [27] added that the accuracy of the dose of pituitary extract greatly determines the success of the fish ovulation process, where the highest dose (1200 mg/kgbb) of broiler pituitary extract gave better results than the doses of 600 and 900 mg/kgbb for Clarias sp., it is suspected that the gonadotropin hormone in the blood will increase with increasing doses injected. Note: A = 0.5 ml/kg BW of Ovaprim (control), B= 0.5 ml/kg BW of chicken pituitary extract, C= 0.5 ml/kg BWof duck pituitary extract, D= 0.25 ml/kg BW of chicken pituitary extract + 0.25 ml/kg BW of duck However, the results showed that the use of local chicken and duck pituitary gland extracts could trigger ovulation in climbing perch, therefore, the local chicken and duck pituitary gland extracts of these avians can be used as an alternative when Ovaprim is not available.…”
Section: Resultsmentioning
confidence: 99%